Biaxially stretchable supercapacitors based on the buckled hybrid fiber electrode array. Issue 29 (2nd July 2015) - Zhang, Nan; Zhou, Weiya; Zhang, Qiang; Luan, Pingshan; Cai, Le; Yang, Feng; Zhang, Xiao; Fan, Qingxia; Zhou, Wenbin; Xiao, Zhuojian; Gu, Xiaogang; Chen, Huiliang; et al.
Abstract : Based on a buckled fiber array and elastic electrolyte, supercapacitors with high capacity, transparency and biaxial stretchability have been developed. Abstract : In order to meet the growing need for smart bionic devices and epidermal electronic systems, biaxial stretchability is essential for energy storage units. Based on porous single-walled carbon nanotube/poly(3, 4-ethylenedioxythiophene) (SWCNT/PEDOT) hybrid fiber, we designed and fabricated a biaxially stretchable supercapacitor, which possesses a unique configuration of the parallel buckled hybrid fiber array. Owing to the reticulate SWCNT film and the improved fabrication technique, the hybrid fiber retained its porous architecture both outwardly and inwardly, manifesting a superior capacity of 215 F g −1 . H3 PO4 -polyvinyl alcohol gel with an optimized component ratio was introduced as both binder and stretchable electrolyte, which contributed to the regularity and stability of the buckled fiber array. The buckled structure and the quasi one-dimensional character of the fibers endow the supercapacitor with 100% stretchability along all directions. In addition, the supercapacitor exhibited good transparency, as well as excellent electrochemical properties and stability after being stretched 5000 times.